Teologi Hosea sebagai Tipologi Konsep Keselamatan dalam Perjanjian Baru - Kornelius Sutriono; Donna Crosnoy Sinaga; Yehuda Mandacan (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2023)
Soteriology is one of the most significant doctrines in Christianity. The theological concept of salvation stands as a central focus within Christian theology. Interestingly, the notion of salvation taught in modern Christian theology relies upon the systematic process of interpreting Biblical teachings. Of course, this dependence rests upon the interpreter's perspective regarding a particular scripture or topic within the Bible. Within Christian literature, there is still a scarcity of biblically-centered investigations into the concept of salvation. This study delves into the theological meaning of salvation based on Old Testament literature, specifically the book of Hosea. Employing a qualitative approach that examines religious documents, this research employs textual and intertextual analysis to construct the concept of salvation within the theology of the book of Hosea. Through a thorough investigation of prophetic actions and orations, it is evident that the theology of the book of Hosea serves as a typology of salvation within the New Testament and is even regarded as a doctrine of Christian salvation in the present day. The emphasis on the theology of reconciliation, redemption, and God's grace emerges as primary values within the theology of the book of Hosea. Despite humanity's inclination towards wrongdoing, God steadfastly commits Himself to bestowing grace, forgiveness, and reconciliation upon them. This is the essence of the Christian concept of salvation.Soteriologi merupakan salah satu doktrin terpeting dalam kekristenan. Konsep teologis tentang keselamatan ini merupakan salah satu pusat dalam teologi Kristen. Menariknya, konsep keselamatan yang diajarkan dalam teologi Kristen modern bergantung pada proses sistematisasi ajaran Alkitab. Tentu saja hal ini bergantung pada sudut pandang penafsir tentang suatu teks atau topik kitab. Dalam literatur Kristen, masih jarang ditemukan adanya penyelidikan secara biblika tentang konsep keselamatan. Penelitian ini mengksplorasi makna teologis tentang keselamatan berdasarkan literatur Perjanjian Lama, yaitu kitab Hosea. Penelitian ini menggunakan pendekatan kualitatif yang meneliti dokumen keagamaan. Analisis tekstual dan intertekstual digunakan untuk mengkonstruksi konsep keselamatan dalam teolog kitab Hosea. Melalui penyelidikan mendalam terhadap tindakan dan orasi profetik, ditemukan fakta bahwa teologi kitab Hosea menjadi tipologi keselamatan dalam Perjanjian Baru, bahkan diyakini sebagai doktrin keselamatan Kristen pada masa kini. Penekanan pada teologi rekonsiliasi, penebusan dan anugerah Allah menjadi nilai utama dalam teologi kitab Hosea. Meskipun manusia menetapkan diri pada kejahatan, Allah tetap menetapkan diriNya memberikan anugerah, pengampunan dan pendamaian bagi mereka. Inilah hakikat konsep keselamatan Kristen.